THE CORRELATION OF STUNTING WITH THE LEARNING ACHIEVEMENT OF ELEMENTARY SCHOOL CHILDREN IN AMANSARI 1 STATE ELEMENTARY SCHOOL - Dwi Pratiwi, Elistiani; Arabta M. Peraten Pelawi; Rotua Suriany Simamora (Soscience: Jurnal Ilmu Sosial Science, 2025)
Stunting is a condition in which children have a height, weight that is not suitable for children their age compared to their age. Stunting describes a state of chronic malnutrition in which the supply of nutrients needed by the body, including the brain, is reduced. Because brain development is not optimal, it can affect the cognitive development of children, children's performance at school, and their learning abilities and consequently affect children's learning achievement in school. Low nutritional status in children will have a negative impact on improving the quality of human resources. Chronic malnutrition is very influential on the achievement of students' academic scores in schools that are getting lower. Research Objectives : This study aims to determine the relationship between stunting and learning achievement of elementary school children at SD Negeri Amansari 1. Research Methods : The research method used is quantitative in nature by using a cross-sectional analytic research design. The population in this study were students in grades 3, 4 and 5 of elementary school, using stratified random sampling technique. Research Results : Based on the results of statistical analysis using the Chi Square Test, it was obtained that the P Value (0.001) was value (0.05). This shows that there is a relationship between stunting and the learning achievement of elementary school children at SD Negeri Amansari 1. Conclusion : There is a relationship between stunting and learning achievement of elementary school children at SD Negeri Amansari 1.